Participation and clarity of budget targets, management accounting information system on managerial performance with budgetary slack as a mediation variable - Wigati, Retno; Rustiana, Siti Hamidah; Dyarini, Dyarini (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
The aim of this research is to analyze